Quote:

1. (x squared -x -20) =0

x=5,-4

$\displaystyle \begin{aligned}

x^2 - x - 20 &= 0 \\

(x - 5)(x + 4) &= 0 \\

x &= 5 \\

x &= -4

\end{aligned}$

Correct!

Quote:

2. 2x squared = 7x +15

x= -3/2, 5

$\displaystyle \begin{aligned}

2x^2 = 7x + 15 \\

2x^2 - 7x - 15 &= 0 \\

(2x + 3)(x - 5) &= 0 \\

x &= -3/2 \\

x &= 5

\end{aligned}$

Correct!

Quote:

3. (2x +1) (x+3) = 42

x= -13/2, 3

$\displaystyle \begin{aligned}

(2x +1) (x+3) &= 42 \\

2x^2 + 7x + 3 &= 42 \\

2x^2 + 7x - 39 &= 0 \\

(2x^2 + 13)(x - 3) &= 0 \\

x &= -13/2 \\

x &= 3

\end{aligned}$

Correct!

Quote:

4. (x) (x-5) = 66

x= 11, -6

$\displaystyle \begin{aligned}

x(x - 5) &= 66 \\

x^2 - 5x &= 66 \\

x^2 - 5x - 66 &= 0 \\

(x - 11)(x + 6) &= 0 \\

x &= 11 \\

x &= -6

\end{aligned}$

Correct!

01